Dampak Kenaikan Muka Air Laut Akibat Perubahan Iklim di Kabupaten Panimbang: Proyeksi Berdasarkan Model CMIP6 - Mardeny, Nabila Sukma; Anzani, Luthfi; Rosalia, Ayang Armelita; Rahman, M. Arief (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
One of the procedures for rescuing a seaplane after an operational is to secure it, namely by mooring at an available port or mooring at a mooring buoy. This mooring buoy is considered a vehicle necessary for securing seaplanes in coastal conditions where it is not yet possible to build infrastructure in the form of an amphiport. To overcome this problem, seaplanes need to add a mooring cleat at the end of the bow of each float, which attaches the rope to the mooring buoy itself. So, it is necessary to study the strength of the mooring cleat itself when withstanding environmental loads. This study was carried out by modelling the mooring cleat using the finite element method to determine where the most significant stresses occur in the mooring cleat structure. Mooring cleats are modelled on deck thickness with varying thicknesses of 20mm and 40mm. The stress that occurred in the mooring cleat structure is then calculated using the Palmgren-Miner rule to determine the fatigue life of the mooring cleat for each variation. It was found that the largest von Misses stress experienced by the structure using 7075-T6 aluminium material was 147.87 MPa, which occurred in the mooring cleat, which was located on the 20mm deck thickness variation at the portside. Meanwhile, this variation's most extended fatigue life calculation occurred for the 40mm deck thickness variation on the portside with 514.43 years.